1989
DOI: 10.1007/bf01410191
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polymethylmethacrylate latices in non-polar media

Abstract: Abstract:The dispersion polymerization of methylmethacrylate stabilized by poly(12-hydroxy-stearic acid) in hydrocarbon media has been investigated. Unlike earlier results [7] it was found that stable latex particles can be prepared in the initial monomer concentration range 8.5 % to 34 %'. To obtain stable particles varying amounts of stabilizer were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…Although the original report was found in the patent literature, the work by Antl et al [38] has been taken as reference in most of the academic publications. [39,41,42,57,58] Using this approach, PHSA homopolymer ( Figure 6) was firstly prepared by polycondensation of 12-hydroxy stearic acid in toluene, usually in the presence of a sulphonic acid catalyst, such as methane sulfonic acid. To achieve sufficient conversion and avoid hydrolysis (i.e.…”
Section: Stabilizer Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Although the original report was found in the patent literature, the work by Antl et al [38] has been taken as reference in most of the academic publications. [39,41,42,57,58] Using this approach, PHSA homopolymer ( Figure 6) was firstly prepared by polycondensation of 12-hydroxy stearic acid in toluene, usually in the presence of a sulphonic acid catalyst, such as methane sulfonic acid. To achieve sufficient conversion and avoid hydrolysis (i.e.…”
Section: Stabilizer Synthesismentioning
confidence: 99%
“…The polymerization is thermically initiated (80°C) and kept under an inert atmosphere at all times, following the procedure of Antl et al [38] and subsequent research reports. [39,41,42,58] Cairns et al [57] also reported a seeded polymerization which involves the early formation of seeded latex and a subsequent slow continuous introduction of a feed solution. After the latex formation is complete (typically 2 hours), and in order to prevent possible desorption of stabilizer from the latex particle surface, the PHSA-g-PMMA-PGMA copolymer is chemically reacted to the particle surface (second step).…”
Section: Using Phsa-g-pmma-pgmamentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of homogeneous fluorescent latex particles as described in this section was done analogous to the methods described in (10,19,20). For the synthesis a standard reflux setup was built.…”
Section: Preparation Of Fluorescent Pmma-latex Via a Single-step Syntmentioning
confidence: 99%